2018
DOI: 10.18203/2394-6040.ijcmph20182606
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of dietary practices and nutritional status among diabetic type II patients in Kiambu County, Kenya

Abstract: Background: Diabetes type 2 has become a serious global health threat due to its increasing prevalence particularly among African countries. Numerous scientific evidence points out on the importance of an individual’s dietary practices and nutritional status in its prevention and management. The objective of the study was to identify the predictors of dietary practices and nutritional status among diabetes type 2 patients.Methods: This was a cross-sectional study and a total of 153 study subjects were recruite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
3
2
0
Order By: Relevance
“…Patients who had not attended formal education and being at primary education were more likely to have poor dietary practice as compared with college graduates and above, respectively. The finding was consistent with a study conducted in Kenya and Bahir Dar [ 30 , 51 ]. This might be because the patients' educational status had a direct relation with their dietary practice.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Patients who had not attended formal education and being at primary education were more likely to have poor dietary practice as compared with college graduates and above, respectively. The finding was consistent with a study conducted in Kenya and Bahir Dar [ 30 , 51 ]. This might be because the patients' educational status had a direct relation with their dietary practice.…”
Section: Discussionsupporting
confidence: 93%
“…It is evident that the dissemination of appropriate information is vital and the first step to make healthy choices. A study performed in Kenya reported that good dietary practice and higher dietary diversity among patients were associated with better nutrition knowledge [ 51 ]. The result of this study implied that diabetic patients' dietary practice was undesirably colossal.…”
Section: Discussionmentioning
confidence: 99%
“…Mothers engaged in government work were seven times more likely to practice good dietary practice than house wives (AOR = 7.2, 3.9, 17.09). This finding is supported by a previous study conducted in Kenya [ 15 ] and in Addis Ababa [ 16 ]. The reason might be that those mothers engaged in government work may be more accessible to get more information about the diet during pregnancy and they may adhere to practice more than house wives.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, in this study, women's dietary knowledge had shown a positive relationship with dietary practice of mothers during pregnancy (AOR = 8.5, 2.19–21.05). This finding is supported by the study conducted in West Gojjam [ 9 ], Kenya [ 15 ], and Addis Ababa [ 16 ]. The reason behind the similarity might be due to the fact that when the women is exposed to dietary information, they may be informed of the consequences of undernutrition on their children, as well as on themselves, and they will more enforced to practice adequate diet.…”
Section: Discussionsupporting
confidence: 72%
“…It has been argued that nutrition knowledge is a necessary but not a sufficient factor for changes in consumers' food behaviours (10) . However, a recent cross-sectional study in Kenya revealed that dietary knowledge, level of education, occupation and income influence dietary practices in people with T2DM (11) . Besides these population-based findings, international guidelines recommend individualised assessment for adults with diabetes (12)(13)(14) .…”
mentioning
confidence: 98%